2012
DOI: 10.4415/ann_12_03_03
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and older people. The European project VINTAGE: Good Health into Older Age. Design, methods and major results

Abstract: Abstract.Objectives. The European project VINTAGE -Good Health Into Older Age aims at filling the knowledge gap and building capacity on alcohol and the elderly, encouraging evidence-and experience-based interventions. Methods. Systematic review of scientific literature on the impact of alcohol on older people; ad hoc survey and review of grey literature to collect EU examples of good practices for prevention; dissemination of findings to stakeholders involved in the field of alcohol, aging or public health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In March 2009, for example, the VINTAGE project, which is funded by the European Union and coordinated by the Istituto Superiore de Sanità (Italy), was started as a ‘part of the ongoing process that recognized the importance of the social and health impact associated with harmful alcohol consumption among the elderly and the necessity to fill the knowledge gap in this issue'. VINTAGE has the main goal to ‘build capacity at the European, country and local levels by providing the evidence base and collecting best practices to prevent the harmful use of alcohol amongst older people' [52,53]. …”
Section: Discussionmentioning
confidence: 99%
“…In March 2009, for example, the VINTAGE project, which is funded by the European Union and coordinated by the Istituto Superiore de Sanità (Italy), was started as a ‘part of the ongoing process that recognized the importance of the social and health impact associated with harmful alcohol consumption among the elderly and the necessity to fill the knowledge gap in this issue'. VINTAGE has the main goal to ‘build capacity at the European, country and local levels by providing the evidence base and collecting best practices to prevent the harmful use of alcohol amongst older people' [52,53]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, alcohol misuse in the elderly is often underestimated, misdiagnosed and undertreated since screening instruments, diagnostic criteria, and public health initiatives are mainly focused on younger age groups. In addition, the average age of the world's population is increasing at an unprecedented rate [33]. During the Swedish Presidency of the council of the European Union (EU) a report concerning alcohol consumption trends and related harms among elderly EU citizens aged over 60 was commissioned by the EU Ministry of Health and Social Affairs [34].…”
Section: Wwwjceionlineorgmentioning
confidence: 99%
“…The main findings about alcohol consumption trends and related harms from the ten EU Member States that contributed to the report (Czech Republic, Finland, Germany, Italy, Latvia, Poland, Slovenia, Spain, Sweden, and The United Kingdom) showed that alcohol use in old age is an under-researched area, even though most elderly Europeans drink alcohol (about 70-80% of men and 50% of women consumed alcohol during the previous year). Alcohol related deaths among elderly Europeans have increased over the past ten years in at least seven of the ten EU Member States surveyed, from 25% in Poland to more than 100% in the UK [33].…”
Section: Wwwjceionlineorgmentioning
confidence: 99%
“…Although alcohol problems and ageing is an under-researched area, a few quantitative studies have been conducted. These studies suggest that alcohol consumption as well as overall alcohol-related problems are increasing among those aged 50 years and older, both in Sweden and in other Nordic and Western countries (e.g., Galluzzo et al, 2012 ; Hallgren et al, 2009 ; Jyrkämä & Haapamäki, 2008 ; Raninen et al, 2013 ).…”
Section: Previous Researchmentioning
confidence: 99%
“…Research suggests, however, that drinking and alcohol-related problems are on the increase among people aged 50 years and older in Sweden and other European countries. The increase among women is particularly recognised (e.g., Galluzzo et al, 2012 ; Hallgren, Högberg, & Andréasson, 2009 ; Jyrkämä & Haapamäki, 2008 ; Raninen, Leifman, & Ramstedt, 2013 ). Increasing drinking problems among people in later life indicates that the pressure on health and social services will increase in the near future ( Ahlström, 2008 ; Gilhooly, 2005 ; O’Connell, Chin, Cunningham, & Lawlor, 2003 ; Socialstyrelsen, 2015 ).…”
mentioning
confidence: 99%